Reality as the leading cause of stress: rethinking the impact of chronic stress in nature - Boonstra, Rudy (Functional ecology, 2013)
1. Chronic activation of the stress axis caused by long-term uncontrollable and unpredictable factors in the environment has been regarded as causing maladaptive and/or pathological effects, both by those studying animals in the laboratory and in nature. While pathology may apply to the former, I argue that it does not apply to the latter. 2. Our thinking on the role of chronic stress in animals in nature has been heavily influenced by biomedical research, but much less so by the ecological and evolutionary context within which animals actually function. I argue that when such stressors occur (e.g. periods of high predation risk, food limitation, prolonged severe weather, social conflict, etc.), although the animal may be chronically stressed, its responses are adaptive and continue to promote fitness. 3. Chronic stressors in nature can be subdivided into whether they are reactive (direct physiological challenges threatening homeostasis and not requiring cognitive processing — for example, food limitation) or anticipatory (perceived to be threatening and requiring cognitive processing — for example, high predation risk). For anticipatory stressors, their impact on the animal should not be based on their absolute duration (they may be acute), but rather by the duration of their physiological consequences. 4. The anticipatory stressor of persistent high predation risk does not elicit chronic stress in all prey classes. Cyclic snowshoe hare and arctic ground squirrels exhibit evidence of chronic stress when predator numbers are high, but cyclic vole and noncyclic elk populations do not. I suggest that chronic stress has evolved to benefit the fitness of the former and not the later, with the key factors being lifespan and life history. I propose that chronic stress evolves in a species only if it is adaptive.